The Role of Customer Satisfaction in Mediating the Influence of Service Quality and Price on Reuse Decisions at Nissan Indomobil Car Workshop Madiun - Afif Firdaus; Tin Agustina Karnawati; Teguh Widodo (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the influence of service quality and price on the decision to reuse car workshop services, with customer satisfaction as a mediating variable. The research is grounded in the importance of automotive service quality in maintaining customer loyalty through improved service and competitive pricing. The population of this study includes customers of Nissan Indomobil Car Workshop in Madiun who have used the service more than once within one year. A total of 128 respondents were selected using purposive sampling. Data were analyzed using a quantitative approach with the Partial Least Squares (PLS) method via SmartPLS 3.0 software. The results reveal that: (1) Service quality and price have a positive and significant effect on customer satisfaction, (2) Service quality, price, and customer satisfaction significantly influence the decision to reuse the service, and (3) Customer satisfaction significantly mediates the effect of service quality and price on the reuse decision.